Relationship Between Eosinophil Levels and Histopathological Grading of Colorectal Carcinoma - Mubdi, Abdul; Muthma'innah, Gadista Mayssi; Wahid, Syarifuddin (Journal La Medihealtico, 2025)
Colorectal cancer (CRC) is a multifactorial disease and a leading cause of cancer-related mortality. CRC ranks as the second most common cancer globally and the third most frequently diagnosed malignancy worldwide. Several studies have suggested that elevated eosinophil levels in peripheral blood correlate with poor prognosis in colorectal cancer cases. This study aims to analyze the relationship between eosinophil levels and histopathological grading of colorectal carcinoma by evaluating peripheral blood eosinophil counts in correlation with CRC histopathology grading. This research employs a descriptive-correlational approach, utilizing univariate and bivariate analyses. The study findings indicate a significant correlation between eosinophil levels and histopathological grading of colorectal carcinoma at Wahidin Sudirohusodo General Hospital, Makassar.